SCIENTIFIC MENTORING AS A KIND OF PARTNERSHIP INTERACTION IN A MODERN UNIVERSITY - Tadeush, Olena (Educological discourse, 2022)
The article reveals the essential characteristics of the process of scientific mentoring as a type of partnership in a modern university; It is determined that research activity in a modern university is one of the most important forms of educational process, which improves the quality of training of future professionals, promotes the ability to use the latest advances in scientific, technical and cultural progress, promotes the maximum development of creative thinking, individual qualities, research skills of students, develops scientific intuition and creative approach to the perception of knowledge and their practical use to solve scientific problems, organizational, technical and applied problems and provides skills for independent research and more. It is noted that increasing the productivity of the research process in modern conditions requires the focus of this process on joint research activities on the basis of partnership, which involves adherence to ethics of communication, taking into account psychological characteristics, social characteristics and its values and values, factors of productive partnership. It is substantiated that mentoring in science acts as a component of professional activity of teachers aimed at activating the content characteristics of all structural components of pedagogical interaction and stimulating the development process through research activities of educational subjects at all stages of their individual and social formation and self-affirmation. It is determined that the main task of scientific mentoring is to direct higher education students to actualize their potential personal capabilities by immersing them in the scientific environment for effective acquisition of knowledge, development and acquisition of new skills, building a scenario of their own optimistic and successful self-actualization life strategy. A fragment of the research results on the attitude of students to personal and professional qualities in the process of research work with mentors. The results of the diagnosis showed that an important task of scientific mentoring at the university is the development of scientific mentors a new style of pedagogical thinking.